Multichannel Information and Choice Overload, Decision Fatigue, and Delayed Purchase Decisions Among Gen Z Consumers - Ketut Ari Satya Utami; Putu Dyah Permatha Korry; Kadek Wulandari Laksmi P; I Gusti Ngurah Oka Ariwangsa (Politeknik Siber Cerdika Internasional, 2026)
Background: The high level of transactions that are not completed in the digital shopping process shows a gap between consumer interest and the realization of final purchases. Data covering 200 million customers from Dynamic Yield shows that the global shopping cart abandonment rate remains relatively high at 76.99%. At the regional level, Asia-Pacific (APAC) recorded the highest abandonment rate at 79.94%, followed by EMEA at 79.02% and the Americas at 73.25%. The data indicate that most consumers who place products in the cart do not complete the purchase process. Objective: This study aims to examine the effects of information overload and choice overload on delay purchase decisions, with decision fatigue serving as a mediating variable among Generation Z consumers in selecting sunscreen products in Bali Province, Indonesia. Method: The study employed a quantitative approach using a survey method by distributing questionnaires to Generation Z consumers who had previously searched for information and considered purchasing sunscreen products. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Result: The findings reveal that information overload has a positive and significant effect on both delay purchase decisions and decision fatigue. Meanwhile, choice overload has a positive but insignificant effect on delay purchase decisions, while exerting a positive and significant effect on decision fatigue. The results further indicate that decision fatigue has a positive and significant effect on delay purchase decisions. Moreover, decision fatigue is proven to mediate the relationships between information overload and delay purchase decisions, as well as between choice overload and delay purchase decisions. These findings reinforce the Stimulus–Organism–Response (S-O-R) Theory and Cognitive Load Theory in explaining the purchasing behavior of Generation Z consumers in digital environments characterized by abundant information and extensive product choices. Conclusion: This study is expected to provide practical implications for the skincare industry and digital platforms in designing more effective marketing communication strategies that minimize consumers' cognitive burden.